Striving for Global Stability: Establishing a New IFAC Agenda: Panel Proposal. Issue 29 (2016) - Stapleton, Amy; Stapleton, Larry; Groumpos, Petros; Jesse, Norbert
Abstract: This paper reports the proceedings of the panel session and reflective group sessions at TECIS 2016 held in Durres in October 2016. The primary goal of the panel was explore both interdisciplinary and intergenerational perspectives on current international instability challenges in order to put in place concrete TC9.5 actions for future engagement within its membership and with external agencies. Contributions were offered from the NGO sector, industry and academics, and included various national perspectives, and contributions from young and older members. The session arose from a proposal by Amy Stapleton, coordinator of the Young Members Forum formally established at TECIS 2015. This work on from findings of previous panels in previous TC9-5 conferences and guidance from the IFAC Technical Board which emphasised a multi-disciplinary approach to international stability issues. The following paper sets out the main contributions and insights from the panel.